2013
DOI: 10.1186/1477-7827-11-15
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine enhances cell proliferation and reduces apoptosis in human endometrial RL95-2 cells

Abstract: BackgroundL-arginine is considered to be one of the most versatile amino acids due to the fact that it serves as a precursor for many important molecules in cellular physiology. When supplemented in the diet, L-arginine can increase the number of implantation sites in mice and rats, suggesting an effect at the level of the endometrium. To this end, this study determined the effect that L-arginine has on apoptosis and cell proliferation in human endometrial RL95-2 cells.ResultsL-arginine at physiological (200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 73 publications
4
34
0
1
Order By: Relevance
“…The elevation of ornithine level may lead to the proliferation of cancer cells by decreasing apoptosis and cell death. [19] At the same time, cancer cells release excessive amount of NOS. Increased NO levels lead to an increase in peroxynitrite radicals, a decrease in T cell-related apoptosis and a proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of ornithine level may lead to the proliferation of cancer cells by decreasing apoptosis and cell death. [19] At the same time, cancer cells release excessive amount of NOS. Increased NO levels lead to an increase in peroxynitrite radicals, a decrease in T cell-related apoptosis and a proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic cells were visualized by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) method (Greene et al, 2013). Proliferation (apoptosis) index was equal to the number of Ki-67-positive cells (apoptotic bodies) assessed per 100 random nuclei.…”
Section: Proliferation and Apoptosis Assaysmentioning
confidence: 99%
“…GnRH analogs have been proven as effective factors in the treatment of endometriosis and adenomyosis by regulating the secretion of estradiol, resulting in marked reduction in NO production and peroxynitrite formation (Kamada et al 2000). Recently, Greene et al (2013) showed the regulatory role of Larginine in NO-mediated enhancement of endometrial growth through increased BAD phosphorylation, which is accompanied by reduced apoptosis. Nevertheless, further studies are necessary to elucidate the significance of NO in the pathogenesis of endometriosis.…”
Section: Pleiotropic Activities Of No In the Endometriummentioning
confidence: 99%